Topoisomerase IIα inhibitory and antiproliferative activity of dihydroxylated 2, 6-diphenyl-4-fluorophenylpyridines: Design, synthesis, and structure-activity relationships. (15th March 2022) - Kunwar, Surendra; Hwang, Soo-Yeon; Katila, Pramila; Man Kadayat, Tara; Jung, Ah-Reum; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: Highlights: Synthesis of fluorine functionalities substituted 2, 4, 6-triphenylpyridines. Strong antiproliferative activity by compounds 11, 12, 37, 50, and 51. Compound 18 as potent topo IIα inhibitor with considerable antiproliferative effect. 4-Trifluoromethoxyphenyl substitution is important for antiproliferative activity. Abstract: A new series of fifty-four 2-phenol-4-aryl-6-hydroxyphenylpyridines containing fluorophenyl, trifluoromethylphenyl, and trifluoromethoxy phenyl groups were synthesized and tested for topoisomerase IIα inhibitory and antiproliferative activity against different cancer cell lines in an attempt to look into topoisomerase IIα-targeted prospective anticancer agents to counter the limitations of available treatment options. When compared to positive controls, several compounds 11 –12, 37, 50, and 51 showed high antiproliferative activity, while several 4-fluorophenyl substituted compounds 13 –14 and 18 showed strong topoisomerase IIα inhibition. Surprisingly, most of the compounds had a significant antiproliferative effect on the HCT15 colorectal adenocarcinoma and T47D breast cancer cell lines. Moreover, compound 12 with para -fluorophenyl at the 4-position and meta -phenolic groups at the 2- and 6-positions inhibited proliferating HeLa cervix adenocarcinoma cells with an IC50 value of 1.28 μM. Based on biological results, the structure–activity relationships of the synthesized derivatives emphasized the significance of 4-trifluoromethoxyphenyl groups for strong antiproliferative activity and 4-fluorophenyl groups for strong topo IIα inhibition. Furthermore, meta - and para -phenolic groups at the 2- and 4-positions are favorable for strong topo IIα inhibitory and antiproliferative activity. The research findings provide insight into the effect of different fluorine functionalities in the discovery of novel topoisomerase IIα-targeted anticancer agents.